المعاهدات الدولية في ظل قواعد القانون الدولي - Obaid Ebraheim Obaid Alkaabi,; Azman Ab. Rahman; Ahmad Zaki Bin Salleh (Universiti Sains Islam Malaysia, 2024)
Date: 9 September 2021 Platform: MSTeams, USIM Nilai, Negeri Sembilan, Malaysia.